PRIVATE EQUITY MARKET IN THE ECOSYSTEM OF START-UPS AND SME SECTOR – PART 2 - Waściński, Tadeusz; Dudkowska, Anna; Kurovs, Jevgenijs (Management and Administration Journal, 2020)
The second part of the article, whose aim is to present the PE market and its significance in young business development, presents PE / VC Funds as an alternative and more risky capital investment and describes a relation between VC funds and startups that use their support. It draws attention to the selection of the fund appropriate for the company’s business profile and the importance of market knowledge. The article shows the most commonly used contractual clauses and it recommends young businesses to use lawyers support while negotiating with investors. It also presents the advantages and disadvantages of introducing the PE investor to the company, which on the one hand is a restriction on the freedom of action for business owners and originators but on the other hand, in the absence of creditworthiness, this is often the only chance to raise capital, develop and survive. In Addition, the managerial support and networking offered by the Funds allow for dynamic growth of the company’s value.